2020
DOI: 10.1097/md.0000000000020903
|View full text |Cite
|
Sign up to set email alerts
|

Value of ultrasonography in the diagnosis of carpal tunnel syndrome—a new ultrasonographic index in carpal tunnel syndrome diagnosis

Abstract: We analyze the effectiveness of ultrasonography in diagnosing carpal tunnel syndrome (CTS) and propose the use of sonographic index of median nerve (MN) in carpal tunnel (SIMNCT) in a diagnostic algorithm and in establishing a scale of severity. We studied a group of 344 patients with CTS symptoms, examining them by ultrasound. We measured in all patients, on the affected hand: the size of the cross-sectional area of the MN at carpal tunnel (CT) inlet and outlet, nerve morphology at passage through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…29 Pert ¸ea et al recently reported a method of diagnosing CTS using almost the same formula as ours based on measurements obtained from a sagittal ultrasonographic image of the median nerve. 13 They reported that a stenosis rate of 16% or greater had a sensitivity of 94.81% and specificity of The present study had some limitations. First, the sample size was small.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…29 Pert ¸ea et al recently reported a method of diagnosing CTS using almost the same formula as ours based on measurements obtained from a sagittal ultrasonographic image of the median nerve. 13 They reported that a stenosis rate of 16% or greater had a sensitivity of 94.81% and specificity of The present study had some limitations. First, the sample size was small.…”
Section: Discussionmentioning
confidence: 66%
“…11 Several studies have shown that morphological changes of the median nerve (stenosis of the median nerve in the distal carpal tunnel and swelling of the median nerve in the proximal carpal tunnel) were observed on sagittal ultrasonographic examination of patients with CTS. [7][8][9][11][12][13] In a study similar to ours, the ideal cut-off values of the MND for the diagnosis of CTS on sagittal ultrasonography were reported to be 2.235 mm for the proximal carpal tunnel and 1.755 mm for the distal carpal tunnel. 7 Furthermore, another study reported that these morphological changes of the median nerve on sagittal images were observed in 90% of patients with CTS.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The diagnostic tests evaluated and their weighted mean sensitivity and specificity are outlined in Tables 2 and 3. 16-128 Although studies utilizing “clinical diagnosis” as a reference standard were treated as a unified subset, many studies 16-128 were found to utilize different definitions of clinical diagnosis. An outline of the utilized definitions for “clinical diagnosis” is presented in Supplemental Digital Content 1.…”
Section: Resultsmentioning
confidence: 99%